(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
Polymeric micelles self-assembled from amphiphilic block copolymers have been intensively investigated as nano-carrier systems for tumor-targeted drug delivery. Diblock copolymers PEO-b-PAAm (DBC) and thriblock copolymers PAAm-b-PEO-b-PAAm (TBC) contained biocompatible chemically complementary polyacrylamide and poly(ethylene oxide) formed micellar structures in aqueous solutions which have hydrophobic complex "core" formed by the hydrogen-bonded PEO/PAAm chains and hydrophilic "corona" of the surplus segments of PAAm blocks. The ability of DBCs and TBCs to bind the anticancer drug doxorubicin was established. This opened the new prospects for using such copolymers as nanocontainers for toxic and poorly soluble drugs. Successful implementation of DBC and TBC micelles for drug delivery requires the presence a special vectors, particularly galactose, in the micellar "corona". Such vectors can recognize corresponding receptors on a cellular surface, interact with them, and penetrate into the intracellular space by the endocytosis pathway. In order to introduce the galactose vectors into DBC or TBC micelles, the corona forming PAA blocks have to contain the corresponding active groups, such as –OH, –COO–, –NH2. Therefore, the methods of DBCs (TBCs) functionalization are particularly important since it allows to input the necessary saccharides and also to expand the applications of micellar nanocarriers to encapsulate and delivery of both the drug substances and genetic materials. In the present work, the polymer-analogous conversion of DBCs and TBCs by the acid hydrolysis of PAAm blocks at 50°C was studied. Kinetic investigations of the hydrolysis reaction of DBCs (TBCs) in comparison with pure PAAm were performed by potentiometric titration. It was established that the process of acid hydrolysis of diblock- and thriblock copolymers depends on the blocks length and occurs more intensive in the block copolymers which have longest PEO and PAA chains. The reasons for this phenomenon are discussed. The fact is that hydrolysis of DBCs samples develops efficiently in comparison with TBCs ones attributed to the steric obstacles which appears in TBCs micelles because of their more complicated structure.